An experiment comparing grids and item-by-item formats in web surveys completed through PCs and smartphones. Issue 1 (February 2017) - Revilla, Melanie; Toninelli, Daniele; Ochoa, Carlos
Highlights: The device used to answer web surveys should be taken into account. Similar levels of interitem correlations are found in PCs and smartphones. Longer completion times are found for grid questions for smartphone respondents. Sometimes less non-differentiation is observed for PCs. Using item-by-item format for all devices is a way to improve comparability. Abstract: Some respondents already complete web surveys via mobile devices. These devices vary at several levels from PCs. In particular, we expect differences when grid questions are used due to the lower visibility on mobile devices and because in questionnaires optimized to be completed through smartphones, grids are split up into an item-by-item format. This paper reports the results of a two-wave experiment conducted in Spain in 2015, comparing three groups: PCs, smartphones not-optimized, or smartphones optimized. We found similar levels of interitem correlations, longer completion times for grid questions for smartphone respondents, and sometimes less non-differentiation for PCs. Thus, using the item-by-item format for smartphones and PCs seems the most appropriate way to improve comparability.